2010
DOI: 10.3851/imp1644
|View full text |Cite
|
Sign up to set email alerts
|

Self-reported adherence is more predictive of virological treatment response among patients with a lower tendency towards socially desirable responding

Abstract: Stratifying patients according to their socially desirable response set improved the prediction of virological treatment response by self-reported adherence. This finding emphasizes the importance of discussing medication adherence with patients in a non-threatening and non-judgemental way that normalizes non-adherence in order to reduce socially desirable responding.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
35
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(37 citation statements)
references
References 11 publications
(19 reference statements)
1
35
0
Order By: Relevance
“…Self-report is most commonly used [22] because it is inexpensive, feasible in a wide variety of settings, and is clinically applicable. Yet it tends to overestimate adherence [23,24] because of recall bias or a desire to please the treatment provider and prevent criticism [25,26]. Aside from these problems associated with measurement, it is also not clear what individual-and structural-level factors are associated with greater levels of adherence.…”
Section: Introductionmentioning
confidence: 94%
“…Self-report is most commonly used [22] because it is inexpensive, feasible in a wide variety of settings, and is clinically applicable. Yet it tends to overestimate adherence [23,24] because of recall bias or a desire to please the treatment provider and prevent criticism [25,26]. Aside from these problems associated with measurement, it is also not clear what individual-and structural-level factors are associated with greater levels of adherence.…”
Section: Introductionmentioning
confidence: 94%
“…Determining the optimal recall period requires balancing shorter intervals (to improve recall/estimation) with longer intervals (to increase the representativeness of the sampled time period and capture cases of infrequent nonadherence). Studies comparing self-report measures with different recall time frames have determined that 30-day recall intervals reduce ceiling effects relative to shorter intervals [44,68,69,71]. A single-item rating of medication adherence over the last 30 days has been validated against viral load in large HIV patient samples and showed the smallest ceiling effect relative to other self-report measures [44,68,69].…”
Section: Recommendations For Optimizing the Validity Of Self-report Mmentioning
confidence: 99%
“…Nieuwkerk et al [71] used a social desirability scale to stratify a large sample of Dutch HIV patients into those reporting lower vs. higher social desirability concerns. The team found that the relationship between self-report medication adherence and viral load was statistically significant for patients indicating low social desirability concerns, but not for those indicating high social desirability concerns.…”
Section: Recommendations For Optimizing the Validity Of Self-report Mmentioning
confidence: 99%
See 1 more Smart Citation
“…Social desirability bias (responding in a culturally appropriate and acceptable manner 7 ) is considered as a main contributor to false positive self-report of good adherence. 5, 8 Indeed, self-reported adherence has been found to be lower and a better predictor of treatment outcomes (HIV RNA copies/ml) among HIV infected patients with a low tendency than in those with a high tendency towards socially desirable responses. 8 Social desirability bias is more frequent among the elderly, women, minority, less educated individuals, 9, 10 and among those with low socio-economic status.…”
Section: Introductionmentioning
confidence: 99%